PRELIMINARY PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTIBACTERIAL ACTIVITY OF DIFFERENT SOLVENT EXTRACTS OF PLECTRANTHUS BOURNEAE GAMBLE (LAMIACEAE) - Thaniarasu, R; Senthil Kumar, T; Abubacker, M. N; Rao, M. V (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim was to investigate the antibacterial activity of Plectranthus bourneae Gamble (Lamiaceae) using different solvents. Methods: Petroleum ether, chloroform, acetone, ethanol and aqueous leaves extracts at different concentration (25, 50, 75, 100 Î¼g/ml) were evaluated for antibacterial activity using disc diffusion method against some Gram-positive species namely Bacillus subtilis, Clostridium sporogenes, Staphylococcus aureus, Streptococcus mutans, Streptococcus mitis and Gram-negative species Salmonella typhi, Klebsilla pneumoniae, Entrobactor aerogenes, Citrobactor freundii, Escherichia coli. The minimum inhibitory concentration (MIC) and minimum bacterial concentrations (MBC) were determined by serial dilution method. Results: The antibacterial activity results of ethanol extract (50 Î¼g/ml) showed maximum zone of inhibition (26 mm) against S. aureus and MIC value of 0.78 Î¼g/ml and MBC of 1.56 Î¼g/ml whereas aqueous extract was least effective on all the strains. The Gram-positive strains of S. aureus and S. mutans were found to be the most sensitive and resistance on all the extracts. Except S. typhi, Gram-negative bacteria used were less inhibitory effect to all the extracts. Conclusion: The present study concluded that the ethanolic extracts of P. bourneae possess potential antibacterial activities against certain microorganisms. Keywords: Plectranthus bourneae, Antibacterial activity, Disc diffusion method, Lamiaceae.